2023
DOI: 10.29333/iji.2023.16118a
|View full text |Cite
|
Sign up to set email alerts
|

Lampung Language Online Learning during the Covid-19 Outbreak: How are the Teacher’s TPACK Skills?

Abstract: The implementation of online learning at the beginning of the covid-19 outbreak brought up some interference for most teachers and students. Technological Pedagogical Content Knowledge (TPACK) is thought to be the answer for teachers in dealing with current online learning problems. This study aims to explore the TPACK skills of Lampung language teachers and the advantages and problems of online Lampung language classes. A survey method was employed to conduct this study in which a questionnaire consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The findings can be understood in light of previous research, which indicated that the sudden and rapid transition in the educational environment to an online system forced teachers, especially those who did not have time to prepare properly, to try to develop their TPACK by employing OT (Murphy, 2020). The frequency of OT using synchronous and asynchronous teaching, provided teachers with sufficient opportunity to integrate various virtual means in the learning process, such as video files, links and tutorials, that support social interaction and collaboration in the classroom (Ariyani et al ., 2023; Engelbertink et al ., 2020; Masry-Herzallah, 2022; Shamir-Inbal and Blau, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The findings can be understood in light of previous research, which indicated that the sudden and rapid transition in the educational environment to an online system forced teachers, especially those who did not have time to prepare properly, to try to develop their TPACK by employing OT (Murphy, 2020). The frequency of OT using synchronous and asynchronous teaching, provided teachers with sufficient opportunity to integrate various virtual means in the learning process, such as video files, links and tutorials, that support social interaction and collaboration in the classroom (Ariyani et al ., 2023; Engelbertink et al ., 2020; Masry-Herzallah, 2022; Shamir-Inbal and Blau, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of whether teachers are ready or not to move to OT, they have no alternative but to adapt to the new work environment created by the COVID-19 crisis that directly and permanently changes future education (Cheng et al ., 2022). This adaptation can be carried out by improving the teachers' TPACK to use online learning technology (Ariyani et al ., 2023). The current research aimed to discover how a year of OT during the Covid-19 crisis affected the TPACK of both Arab teachers (AT) and Jewish teachers (JT) in Israel.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations